Potencialidades de notícias publicadas por mídias de grande acesso para a incersão de física moderna no ensino médio – o caso LHC - Ortelan, Gabriela Brito (2015)
Scientific discoveries and large experiments usually become object for mass media and scientific disclosure. Contact with this material can, in many ways, contribute to the teacher's work in the classroom. This paper has the objective of studying the potential use of this material in the classroom, through the different dimensions this material can emcompass. Initially, a wide outlook of the insertion of modern and contemporary physics in high school is presented, with it's justifications and challenges. Some characteristics and possibilities for the use of scientific disclosure materials in class are also presented, under the viewpoint of authors located within this interface between education and communication. This paper focuses on what is called the "LHC Case", referring to media material associated to the particle accelerator LHC (Large Hadron Collider), as contextualizing elemnt for particle physics teaching, and also as motivator for other questions, like the relationship between science and society, among other things. A description of a set of newspaper articles about the LHC case published between 2006 and 2013 is presented, as well as a critical analysis of this set, using a few criteria such as the news theme, focus and content. From this analysis of the news, a minicourse was elaborated and ministered for students of UFSCar's college preparatory course, as a space for data collection, with the purpose of evaluating the potential use of media disclosed news in the selection and development of content related to modern physics in high school. Results point at the possibility of the use of news in classes, fulfilling different roles according to the teacher's objective. In the LHC case, the possibility of using news with different characteristics to motivate discussions which establish relations with science, technology and society has proven feasible and interesting, as it can contribute for the construction of a less distorted and more critical view of science, and giving meaning to the teaching of particle physics in high school.